Reviving Waqf-Based Endowments for Sustainable Teacher Training in Northern Nigeria - Adamu Abubakar Muhammad; Abubakar Aliyu Yakub; Usman Jibril Mikail; Muhammad Hamma- Adama Ahmad; Namungo Hamzah; Huma Khan (CV Media Inti Teknologi, 2025)
This study investigates the feasibility of restoring waqf-based endowments as a long-term method for improving teacher education and training in Northern Nigeria. Drawing on historical and present waqf models, the research investigates how this Islamic philanthropic organization might solve teacher shortages, low training quality, and imbalances in educational service delivery. The study employs a qualitative research methodology that includes document analysis, expert interviews, and case studies from various Islamic institutions. The findings show that waqf has historically played an important role in financing education in Muslim communities, but it has fallen due to colonial interruptions, legal limits, and a lack of public awareness. The research suggests that reviving and updating waqf through proper legislation, community participation, and integration with public-private partnerships can considerably improve the quality and accessibility of teacher training in underprivileged areas. Recommendations are provided for government agencies, religious leaders, NGOs, and communities to collaborate in building waqf-based teacher education projects to reposition and assure sustainable teacher training in Northern Nigeria.